Molecular detection and genotyping of chlamydia psittaci in captive psittacines from Costa Rica - Dolz, Gaby (2013)
Oropharyngeal and cloacal swabs from 117 captive psittacine birds presented at veterinary clinics (88) and from shelters/rescue centers of wildlife (29) were collected to determine the prevalence of C. psittaci in captive birds in Costa Rica. Samples were collected during 2009 from a total of 19 different species of parrots, with Ara macao (33), Amazona autumnalis (24), Amazona ochrocephala (21), and Ara ararauna (8) being the most representative species sampled. C. psittaci was detected in four (3.4%) birds using molecular detection (PCR). The positive samples belonged to birds presented at veterinary clinics; three of them were Ara macao and one Amazona ochrocephala. Three birds were adults; all positive birds showed no symptoms of illness and lived in homes with other birds, two in San José and two in Heredia. Sequencing was used to confirm the PCR positive results, showing that two samples of C. psittaci belonged to genotype A, representing the first report of the presence of this genotype in Costa Rica. The detection of this bacterium in captive psittacine birds shows that there is a potential risk for people living or having contact with them and that there is a possibility of infecting other birds.